Kontribusi Bentuk Perceived Social Support terhadap Parenting Stress pada Ibu yang Memiliki Anak Batita di Kota Bandung - Hannah Win Hutabarat; Marissa Chitra Sulastra (Humanitas (Jurnal Psikologi), 2023)
This study was aims to identify the contribution of the type of perceived social support to parenting stress in mother with a child under three-year-old in Bandung. Total participants are 145 persons. This research uses accidental type of sampling. Perceived social support instrument is the adapted from Brigitta Louise (2017), consist of 26 items, validity ranging from 0.330–0.799 and reliability of 0.903. Parenting stress instrument is the adaptation from PSI-SF from Abidin (1995), consist of 34 items, validity ranging from 0.370–0733 and reliability of 0.928. This study was tested using simple regression analysis. Based on the result, all types of perceived social support contribute to parenting stress. Perceived emotional support (R2= 0,203; p= 0,000), perceived instrumental support (R2= 0,041; p= 0,014), perceived informational support (R2= 0,040; p= 0,016), and perceived companionship support (R2= 0,164; p= 0,000). From this study, mothers with a child under three-year-old are advised to be active in seeking the type of social support.